Relaciones de género en la familia y la salud social de la cuidadora del usuario/a del padomi - essalud, sector la esperanza 2014 - Arana Minchan, Lourdes Fiorella (2014)
This research study aims to determine the impact of gender relations within the family, the Social Health User caretake, Programa de Atención Domiciliaria (PADOMI) - ESSALUD - Sector La Esperanza. 2014. Throughout the investigation, use was made of the descriptive design, and to obtain the results of the investigation are worked with a total of 73 carers of users / as Home Care Program District La Esperanza, whose ages are between 25 and 81 years. In data collection, it was necessary to do a comprehensive review of various documentary sources in order to understand the issue under study, thus previously performed research, provided a blueprint for generating new knowledge. It was also essential to make use of various qualitative research techniques (such as observation and interviews) and quantitative (questionnaire); which were indispensable to translate the information gathered and contrast with the assumptions made in the investigation. Using the statistical method was reached to have clarity of reality in which the group is being studied, showing that gender relations within the family deteriorates the social health of caregivers, through limited access to opportunities paid work, because the task of caring and inequity in fulfilling roles; also limiting the participation of this in the space of social interaction, such as friends, politics, community, etc., which help you to have healthy relationships with others and at the same time enjoy a social and mental wellbeing. This thesis analyzes the social health of the caregiver, from general systems theory, which sees the family as a system in its entirety, with constant interaction and where the positive and negative actions also are formed. Also the gender shows social inequality between men and women, and analysis about the construction of female identity and male identity since they are not natural or biological realities, however they are cultural constructions given in the family. And within families carers reflected gender relations of inequality, inequity relegating women and making visible only in the performance of the player in the role and care of dependent people are. It is vital to be clear about the relevance of this study, where the gestation of a model of more equitable and consistent with cultural partners changes care is necessary to establish proposals for change to a visibility of women, and it focused from the perspective of respect for human rights and gender equality in the family.